Current status and influencing factors of sleep disorders in school-age children with asthma - Wei, Jia-Hui; Ju, Ya-Bei (Zhongguo dang dai er ke za zhi, 2025)
To investigate the current status and influencing factors of sleep disorders in school-age children with asthma, providing a scientific basis for improving sleep quality and quality of life of asthmatic children. This study selected school-age children with asthma admitted to the Children's Hospital of Nanjing Medical University from March 2022 to March 2024 as subjects. A questionnaire was used to assess their sleep conditions, and based on the assessment results, the participants were divided into a sleep disorder group (106 children) and a non-sleep disorder group (181 children). Multivariate logistic regression analysis was conducted to identify the influencing factors of sleep disorders in asthmatic children. A total of 287 asthmatic children were included, of which 106 (36.9%) had sleep disorders. Multivariate logistic regression analysis showed that being older than 10 years, obesity, poor medication adherence, unhealthy family functioning, passive smoking, and participation in only some physical activ